PELATIHAN PENGEMASAN PAKET “PETASAN” (PRODUK WISATA PEDESAAN) DI DESA WISATA PENGLIPURAN KECAMATAN BANGLI KABUPATEN BANGLI BALI (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2015)
Bali is famous destination with culture and hospitality of the community is a unique thing that is always sought after by tourists, in addition to the natural beauty and diversity of its tourist attraction. Penglipuran is one village in Bali which has characteristics such as Bali Aga social institution. The purpose of this activity is to provide training package packaging products rural tourism at the Tourism Village Penglipuran as to anticipate the development of tourism and free trade world. In the implementation of activities carried out for solving the problem is: giving lectures and training regarding tourism and package packaging and communities involved are 40 participants. Based on the potential for tourism, as for rural tourism package in accordance with the potential Penglipuran village that can be created, among other things: 1). Village Tour Package); 2). Trekking Tour Package; 3).Cycling Tour Package; 4). Package Creation Cem-cem healty drinks.